Assessment of the effect of carbon nanohorns on the microviscosity of membranes of erythrocytes and rat plasma proteins by the method of spin probes - Kartel, N.T.; Ivanov, L.V.; Lyapunov, A.N.; Nardid, O.A.; Cherkashina, Ya.O.; Gurova, О.А.; Ocotrub, A.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
By the method of spin probes, we have studied the effect of initial and oxidized carbon nanoshorns on the microviscosity of rat erythrocyte membranes and the viscosity of the water-containing plasma protein matrix. Introduction of nanohorns in a concentration of 100 μg/ml into erythrocyte suspension results in an increase in the membrane microviscosity within four hours (about 60 % effect), increasing the polarity of a microenvironment for lipophilic probes in the outer layer of membrane phospholipids, and a disorder of erythrocyte's membranes. Introduction of nanohorns in plasma leads to a slight reduction in the viscosity of water and the protein matrix, apparently, due to its partial destruction, especially macromolecules of serum albumin. Cytotoxicity of pristine and oxidized nanohorns evaluated by us is higher as compared to the nanoparticles of oxidized graphene, but is significantly lower than the carbon nanotubes, which are capable of dramatically increasing the microviscosity of membranes of erythrocytes and disrupting their integrity.